2021
DOI: 10.3390/ijerph18052673
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Neuromuscular Mechanosensitivity and Chronic Neck Pain in Guitarists: A Cross-Sectional Study

Abstract: Musicians frequently complain of musculoskeletal pain due to high mechanical demands, with the cervical spine being the most affected. Increased neuromuscular mechanosensitivity due to repetitive mechanical stress over time has been described in neck pain patients. Nevertheless, the association between musculoskeletal pain and neuromuscular mechanosensitivity in musicians is unknown. Therefore, the aim of this study was to analyze the relationship between neuromuscular tissue mechanosensitivity and neck pain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The relationship between posture and tissue mechanosensitivity has been studied previously. Although the mechanical stress suffered by the structures involved in a poor posture could produce an alteration of the sensitivity of these structures, it seems that the presence of pain plays an important role in the degree of mechanosensitization [ 7 , 32 , 33 ]. Martinez-Merinero P et al [ 7 ], Rojas VEA et al [ 32 ], and Pacheco J et al [ 33 ], showed that mechanosensitivity of neck muscles and upper extremity nerve trunks is related to neck pain more than to forward head position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between posture and tissue mechanosensitivity has been studied previously. Although the mechanical stress suffered by the structures involved in a poor posture could produce an alteration of the sensitivity of these structures, it seems that the presence of pain plays an important role in the degree of mechanosensitization [ 7 , 32 , 33 ]. Martinez-Merinero P et al [ 7 ], Rojas VEA et al [ 32 ], and Pacheco J et al [ 33 ], showed that mechanosensitivity of neck muscles and upper extremity nerve trunks is related to neck pain more than to forward head position.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanical stress suffered by the structures involved in a poor posture could produce an alteration of the sensitivity of these structures, it seems that the presence of pain plays an important role in the degree of mechanosensitization [ 7 , 32 , 33 ]. Martinez-Merinero P et al [ 7 ], Rojas VEA et al [ 32 ], and Pacheco J et al [ 33 ], showed that mechanosensitivity of neck muscles and upper extremity nerve trunks is related to neck pain more than to forward head position. Similarly, a study conducted by Haik M et al [ 34 ] in which they found that subjects with shoulder pain demonstrated mechanical hyperalgesia compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread hypersensitivity in cervical radiculopathy (142), lumbar radiculopathy (143), whiplash injuries (142,144), and plexopathies after breast cancer surgery and radiotherapy (145) also suggests the etiological importance of proximal compressive nerve injury. Of similar relevance may also be the occurrence of bilateral peripheral hypersensitivity in patients with nonneurogenic neck pain (146) and nonspecific arm pain (147).…”
Section: Distal Vs Proximal Neural Lesionmentioning
confidence: 97%
“…Widespread hypersensitivity in cervical radiculopathy ( 142 ), lumbar radiculopathy ( 143 ), whiplash injuries ( 142 , 144 ), and plexopathies after breast cancer surgery and radiotherapy ( 145 ) also suggests the etiological importance of proximal compressive nerve injury. Of similar relevance may also be the occurrence of bilateral peripheral hypersensitivity in patients with non-neurogenic neck pain ( 146 ) and nonspecific arm pain ( 147 ).…”
Section: Pre-hypothetical Reasoning: Ectopic Nociceptive Sensitizatio...mentioning
confidence: 99%